2013
DOI: 10.3109/13880209.2013.842599
|View full text |Cite
|
Sign up to set email alerts
|

Pro-apoptotic effect ofPersea americanavar.Hass(avocado) on Jurkat lymphoblastic leukemia cells

Abstract: Context: Therapy for leukemia has a limited efficacy. There is a need to search for alternative anti-leukemia therapies. Persea americana Mill var. Hass (Lauraceae) is a tropical fruit (avocado) that might be used against cancer. Objective: To investigate whether P. americana induces death in Jurkat lymphoblastic leukemia cells. Materials and methods: Four ethanol extracts (0.1, 0.5, 1, 2 and 5 mg/mL) from avocado fruit (endocarp, whole seed, seed and leaves) were analyzed against Jurkat cells. Hydrogen peroxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
8
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 28 publications
4
8
0
3
Order By: Relevance
“…Previous results have shown that early stage premalignant cell lines TE1177/HPV16/ E6 and TE1177/HPV16/E7 contain high levels of ROS; incubation with D003 extract increased their basal levels and induced apoptosis, but only caused a small increase in the primary parent TE1177 cells [11]. This was also found to be true in Jurkat lymphoblastic leukemia cells where avocado extract induced ROS-dependent apoptosis [46]. In the current study, we observed that DMBA treated buccal mucosa contained higher levels of ROS and that topical application of avocado D003 extract further increased the ROS levels.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Previous results have shown that early stage premalignant cell lines TE1177/HPV16/ E6 and TE1177/HPV16/E7 contain high levels of ROS; incubation with D003 extract increased their basal levels and induced apoptosis, but only caused a small increase in the primary parent TE1177 cells [11]. This was also found to be true in Jurkat lymphoblastic leukemia cells where avocado extract induced ROS-dependent apoptosis [46]. In the current study, we observed that DMBA treated buccal mucosa contained higher levels of ROS and that topical application of avocado D003 extract further increased the ROS levels.…”
Section: Discussionsupporting
confidence: 63%
“…Garcinol from fruit rind of Garcinia spp., for example, has been found to inhibit cell proliferation in DMBAinduced HCP carcinogenesis [39]. Avocado extract has been shown to: i) inhibit EGRK/RAF/MEK/ERK1/2 pathways [8] and Cyclin D1 (our unpublished data) and over-expression of MEK/ERK1/2 that partially overcomes D003 reduced cell proliferation [8]; ii) up-regulate p21 [7] and our unpublished data); and, iii) enhance ROS and induction of apoptosis [7,11,46]. It has been reported that targeting EGFR in the DMBA/HCP model reduces cell proliferation [47].…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of intracellular ROS production was carried out according to Bonilla-Porras et al [21]. Briefly, 5 × 10 4 cells were incubated with dichlorofluorescein diacetate (DCF-DA) at 10 μM final concentration for 25 min at 37 °C in the dark.…”
Section: Methodsmentioning
confidence: 99%
“…P. americana fruits are commonly known as “avocados.” Nowadays, a likely anticancer activity of P. americana (avocado) seeds, most often thrown away, has generated growing scientific interest. Indeed, the ethanol extract of P. americana seeds was found stimulating apoptosis of Jurkat lymphoblastic cells [ 17 ]. The cytotoxic effect of the same extract was also reported on breast cancer cell line (MCF-7) and human liver cancer cell line (HepG2) [ 18 ].…”
Section: Introductionmentioning
confidence: 99%